An analysis of Pompe newborn screening data: a new prevalence at birth, insight and discussion - Colburn, Ryan; Lapidus, David (Frontiers in Pediatrics, 2024)
This study includes over 11.6M newborns screened (NBS) for Pompe Disease (PD) from 29 distinct universal screening programs across 8 countries and 4 continents. The birth prevalence of PD is 1:18,711, with no evidence of difference across populations of European, Latin American, or Asian ancestry, though differences may exist for PD subtypes. This study also compares these results, based on direct detection of disease and analyzed using a binomial method along with power analysis, with other methods for estimating the ‘frequency’ of rare genetic diseases (such as utilizing Hardy-Weinberg equilibrium on allele frequency and confidence interval analysis). This comparison demonstrates the implications of sample size and frames a discussion on its influence on the reliability of results when extrapolating to a population beyond the study dataset. Objectives Primary: Establish a new figure for prevalence at birth for Pompe disease by collecting and analyzing the largest relevant dataset to date and using that result to project population prevalence at birth in a novel way. Secondary: Compare these results to previous analyses to offer a framework for evaluating ‘frequency’ data that can be applied to other rare, genetic diseases, along with methods to assess quality of estimates.